Long-term expression of human adenosine deaminase in rhesus monkeys transplanted with retrovirus-infected bone-marrow cells. - van Beusechem, V W (1992)
Gene transfer into hemopoietic stem cells could offer a lasting cure for a variety of congenital disorders. As a preclinical test for such a gene therapy, rhesus monkeys were transplanted with autologous bone-marrow cells infected with helper-free recombinant retroviruses carrying the human adenosine deaminase gene. The in vivo regenerative capacity of the infected bone marrow could be conserved, suggesting survival of repopulating hemopoietic stem cells. In the hemopoietic system of transplanted animals the foreign gene could be observed for as long as the animals were analyzed (in two monkeys greater than 1 yr after transplantation). Genetically modified cell types and tissues included peripheral blood mononuclear cells, granulocytes, bone-marrow cells of various densities, and spleen and lymph nodes. The presence of the provirus in the short-living granulocytes greater than 1 yr after bone-marrow transplantation provided evidence for the transduction of very primitive hemopoietic progenitors. Moreover, the gene transfer resulted in sustained production of functional human adenosine deaminase enzyme in peripheral blood mononuclear cells. These results demonstrate the feasibility of bone-marrow gene-therapy approaches, in particular for treating adenosine deaminase deficiency.